2010
DOI: 10.1007/s10067-010-1463-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rheumatologic manifestations of chronic hepatitis C virus infection among Egyptians

Abstract: Chronic hepatitis C virus (HCV) viremia has been known to provoke a plethora of autoimmune syndromes referred to as extrahepatic manifestations of chronic HCV infection. Aim of the current study was to assess the prevalence of rheumatologic manifestations among Egyptians with hepatitis C infection and its' association with cryoglobulin profile. The current research represents a cross-sectional study where patients with chronic HCV infection attending the outpatient clinic of the National Hepatology and Tropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
5
27
0
3
Order By: Relevance
“…In agreement with our study, Mohammed et al [22] showed that 22.7% of patients with HCV-associated arthropathy had arthritis, whereas Bassyouni et al [16] and Orge et al [23] reported that 55 and 47%, respectively, of patients with HCVassociated arthropathy complained of polyarthritis. In agreement with our study, Mohammed et al [22] showed that 22.7% of patients with HCV-associated arthropathy had arthritis, whereas Bassyouni et al [16] and Orge et al [23] reported that 55 and 47%, respectively, of patients with HCVassociated arthropathy complained of polyarthritis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our study, Mohammed et al [22] showed that 22.7% of patients with HCV-associated arthropathy had arthritis, whereas Bassyouni et al [16] and Orge et al [23] reported that 55 and 47%, respectively, of patients with HCVassociated arthropathy complained of polyarthritis. In agreement with our study, Mohammed et al [22] showed that 22.7% of patients with HCV-associated arthropathy had arthritis, whereas Bassyouni et al [16] and Orge et al [23] reported that 55 and 47%, respectively, of patients with HCVassociated arthropathy complained of polyarthritis.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were similar to those of Bassyouni et al [16] and Mohammed et al [22]. The mean alanine aminotransferase and aspartate aminotransferase were higher in HCV patients with arthropathy than in HCV patients without arthropathy and RA patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to hepatic complications, hepatitis C virus (HCV) infection is reported to predispose to extrahepatic disorders involving renal, dermatologic, hematologic and rheumatologic systems [3,4,5] . Articular involvement in HCV infection is a frequent complication varying from 4 to 23% and the clinical picture of HCV related arthropathy varies widely, ranging from polyarthralgia to monoarticular or oligoarticular intermittent arthritis and symmetric chronic polyarthritis [4,5,6] . HCV associated arthritis in contrast to RA has a benign course, typically not deforming and not associated with…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, symptomatic arthralgia has been estimated to occur in 6.5-19% of patients [30][31][32]. Hepatitis C can cause two distinct types of arthritic symptoms: the more common rheumatoid arthritis-like polyarthritis of the small joints but without …”
Section: Hcvmentioning
confidence: 99%